2009
DOI: 10.1002/cncy.20007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ThinPrep cytology in establishing the diagnosis of small cell carcinoma of lung

Abstract: BACKGROUND:ThinPrep liquid‐based cytology (TP) preparations are being used increasingly in nongynecologic specimens. To the authors' knowledge, few studies to date have evaluated TP cytology in the setting of small cell carcinoma of the lung (SCCL). Accurately differentiating SCCL from other lung tumors has important clinical and therapeutic implications. Herein, the authors evaluated the diagnostic utility and cytomorphology of TP in the setting of SCCL.METHODS:All cases of SCCL with prior or concurrent TP cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
43
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 15 publications
4
43
0
1
Order By: Relevance
“…Morphologically we found that smearing and molding were less pronounced in LBC smears in small cell carcinoma lung and some amount of cellular elongation was observed in these cases [19]. The above observation is due to suspension of cells in liquid media.…”
Section: Resultsmentioning
confidence: 67%
“…Morphologically we found that smearing and molding were less pronounced in LBC smears in small cell carcinoma lung and some amount of cellular elongation was observed in these cases [19]. The above observation is due to suspension of cells in liquid media.…”
Section: Resultsmentioning
confidence: 67%
“…2015;139:178-183; doi: 10.5858/ arpa.2013-0282-CP) P ulmonary bronchial brushing (BB) is one of the most sensitive cytological procedures for diagnosing lung cancer. [1][2][3] Specimens obtained by BB can be processed by conventional methods or by liquid-based preparations (LBPs). Although conventional methods are inexpensive, the quality of processing depends heavily on the skills of the individual laboratory staff member.…”
mentioning
confidence: 99%
“…4 In contrast, LBPs generally preserve most cellular details, produce uniform results, and are generally easier to standardize. 2,3 However, cells and cellular groups may round up in LBPs and generate hyperchromatic cells and groups that are difficult to visualize and interpret.…”
mentioning
confidence: 99%
See 2 more Smart Citations